Village Fund Allocation Information System Design - Ardiansyah; Fathurrahmad; Fauzan Putraga Albahri; Bahruni (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2022)
Village development has a very important and strategic role in the context of National Development and Regional Development. In village development, the village government is located as a subsystem of the government administration system in Indonesia, so that the village has the authority, duties and obligations to regulate and manage the interests of its own community. In carrying out the authority, duties, and obligations of the village in the administration of government and development, a source of village income is needed. In the process of managing the Village (Gampong) Fund Allocation, Peukan Bada District, Aceh Besar District, the village government is faced with the condition of the community's education level being still weak. Based on previous research, this research has a purpose, namely to describe and analyze the Management of Village Fund Allocation in empowering rural communities; the driving and inhibiting factors for the management of Village Fund Allocation in empowering rural communities in Peukan Bada District, Aceh Besar District. The objectives to be achieved from this research are; create an online budget data processing information system design, and improve all aspects of data forms or expand the relationship or relationship of each data. The design method used is the waterfall model taking basic activities such as specification, development, validation, and evolution and representing them as phases such as requirements specification, software design, implementation, testing and so on. Based on the results of the analysis and design of the village fund allocation information system, it can be seen that until now it is still done manually. The author can conclude including; the design of the village fund allocation application can provide convenience in carrying out the implementation process of gampong development, and the use of a system that is still manual has limitations in the data storage process, data search and report generation process.